Impacto de las utilidades en precios de acciones: Índice S&P/BVL Perú Select de Bolsa de Valores de Lima 2013 - 2017 - Jiménez Castillo, César Alfonso (2023)
The present research aimed to determine whether earnings positively impact on S&P BVL Perú Select Index stock prices, during the period 2013-2017. First, the reality related to the problem and prior investigations were reviewed. Furthermore, the setting of justification, problem, objectives, related theoretical-conceptual framework and hypothesis, which sustains that earnings have a positive impact on stock prices, was made. Second, the object of study, including sample calculation, as well as the technique of documental analysis of data from Stock Market Superintendence and Lima Stock Exchange, were established. In that sense, instruments Excel and EViews used for statistical and econometric analysis, were explained. Then, methods used were mentioned: inductive-deductive and statistical-econometric. Furthermore, contrast design was descriptive, while data processing and analysis considered Excel and EViews as tools for such ends. On the other hand, independent and dependent variables were studied trough Excel graphs and EViews regressions: Earnings per Share (Var. %), Rate of Earnings Retention (TRU), Return on Equity (ROE) and Stock Price (Var. %). The result indicated that Earnings per Share (Var. %), Net Income (Var. %), Return on Equity (ROE), the three of them with up to 2 lags, and even Stock Price (Var. %) with 1 lag, have an statistically significant and positive relation with the Stock Price (Var. %); whereas TRU was no statistically significant, since its presence derived in either heteroskedasticity or abnormality for all of the regressions. In conclusion, earnings have a positive impact on S&P BVL Peru Select Index stock prices, during the period 2013-2017, in an inefficient form and with predictable prices. Furthermore, it was recommended that use of the research for investment, study or research amplifying ends be made. Finally, bibliographic references were detailed y and annexes were added.